Analysis of the causes and preventive measures of fatal fall-related accidents in the construction industry - Rafindadi, A.D. (Ain Shams University, 2022)
Fall-related accident causes severe injuries and deaths in the construction industry. This study analyzed 108 fall fatalities in Malaysia from 2010 to 2018 to find the critical, relevant variables. The findings revealed that this type of accident occurred most frequently in Johor, Penang, and Kuala Lumpur/Putrajaya, and the most affected trade workers were construction laborers. AHP model for the fall-related accident primary factors and sub-factors was also developed to determine their relative weights and priorities. It was discovered that workers' unsafe actions are the primary essential factor contributing to this accident. Results also show that the most critical sub-factors are financial constraints, job complexity at high altitude, dangerous working procedures, unguarded edges/holes at higher elevations, and rushing to complete the job. The findings could help raise safety awareness about fall-related hazards and provide valuable guides for further effective prevention and management plans in Malaysia and countries with similar characteristics. Â© 2022 THE AUTHORS